THE POLITICAL DIMENSION OF INDONESIAN ISLAMIC EDUCATION IN THE POST-1998 REFORM PERIOD (State Islamic University (UIN) of Sunan Ampel Surabaya, 2014)
In the Indonesian Islamic Education discourse, the state of political atmosphere influences several policies of Islamic Education. In the post-1998 reform period, the role and institutional development of politics affected the way Indonesian Islamic Education were going through in a positive way. The institutional improvement had shifted Islamic Education from the second-cast of education into a higher level. However, Islamic Education has not been at the centre of both elite and popular attention in Indonesia. Therefore, this paper examines policies in Indonesian Islamic Education which reflects upon the substance of its growing political dynamics. Cultural analysis is used in this paper to examine the root of Islamic Education identity.